Manufacturing Mohism in the Mencius - Radice, T. (Asian Philosophy, 2011)
The Mencius contains several negative remarks about the Mohists and their doctrine of 'universal love' (jian'ai). However, little attention has been paid to whether Mencius' descriptions of Mohism were accurate. Fortunately, there is a surviving record of the beliefs of Mozi in the text that bears his name. In this essay, I analyze this text and descriptions of Mohism from other early Chinese texts, and compare them to the criticisms of Mohism in the Mencius. Ultimately, I show that the image of the Mohists as ones who promoted a doctrine that contradicted filial piety was inaccurate, and obscured the complexities of filial piety in the Warring States period. © 2011 Taylor and Francis.
Keywords: dept.his; peer-reviewed